¿Ladrones, pequeños empresarios o trabajadores independientes? K’ajchas, trapiches y plata en el cerro de Potosí en el siglo XVIII - Rossana Barragán R. (Nuevo mundo - Mundos Nuevos, 2015)
This article is a contribution to the history of a group of self-employed workers that produced 20 to 35% of Potosí’s silver in the 18th century. The paper begins remembering the contribution of historiography to the study of the k’ajchas. The analysis is centered then, in the property rights to the mines because these kajchas challenged the ownership of the ores, appearing as “thieves”. The ores exploited by them were transformed in silver in the trapiches or rudimentary mills. This is why the article focus in the ensemble k’ajcha-trapiche that meant the emergence of a quasi-parallel economy that burst into the scene with considerable energy. This is also an example on how workers struggled to have their part in the new economy. In the conclusions there are some thoughts about the problems when it comes to define them and the consequences of the k’ajchas/trapiches for a new unsderstanding of the labour system in Potosi.